2022
DOI: 10.1002/essoar.10512108.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variations in the Ratio of Carbon and Nitrogen Stable Isotopes of Particulate Organic Matter in the Southern Sea of Japan

Abstract: Carbon and nitrogen dynamics in the Sea of Japan (SOJ) are rapidly changing. Here, we investigated the carbon and nitrogen isotope ratios of particulate organic matter (δ 13 C POM and δ 15 N POM , respectively) at a depth of [?] 100 m in the southern part of the SOJ from 2016 to 2021. Both δ 13 C POM and δ 15 N POM showed multimodal distributions and were divided into four classes (I-IV) using the Gaussian mixed model. Most of the samples were categorized into class II (n = 441), with the mean ± standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 52 publications
(84 reference statements)
3
6
0
Order By: Relevance
“…Two recent studies have indicated that the carbon and nitrogen stable isotope ratio of POM varies in the western North Pacific marginal seas (Ho et al, 2021;Kodama et al, 2021). The δ 13 C of POM increased as the phytoplankton abundance increased in the southwestern ECS, which is consistent with isotope fractionation that occurs during photosynthesis (Ho et al, 2021).…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…Two recent studies have indicated that the carbon and nitrogen stable isotope ratio of POM varies in the western North Pacific marginal seas (Ho et al, 2021;Kodama et al, 2021). The δ 13 C of POM increased as the phytoplankton abundance increased in the southwestern ECS, which is consistent with isotope fractionation that occurs during photosynthesis (Ho et al, 2021).…”
Section: Introductionsupporting
confidence: 58%
“…Gao et al (2014) reported the horizontal distribution of δ 13 C and δ 15 N and that δ 13 C largely varies in this sea. Active nitrogen fixation decreases the δ 15 N of POM in offshore waters in the Kuroshio area during the summer, whereas the δ 15 N of POM remains high in the coastal waters (Kodama et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…From literature that exhibited data only in its plots, data were extracted from the plots using WebPlotDigitizer (https://automeris.io/WebPlotDigitizer/). The literature data were mainly distributed in the Pacific coasts, the Kuroshio inshore, the Seto Inland Sea and the East China Sea (Minagawa et al, 2001;Takai et al, 2002;Toyokawa et al, 2003;Wu et al, 2003;Yokoyama and Ishihi, 2003;Kasai et al, 2004;Chen et al, 2006;Hoshika et al, 2006;Yamaguchi et al, 2006;Fukumori et al, 2008;Miller et al, 2010;Sano et al, 2013;Chang et al, 2014;Mino et al, 2016;Mei, 2018;Ho et al, 2021;2022b;Nakamura et al, 2022). Unpublished isotope data from POM, collected during research surveys conducted by the University of Tokyo and the Japan Fisheries Research and Education Institute in the western North Pacific and its marginal seas during 2013-2021, were added to the data set (Supplementary Table 1).…”
Section: Pom Data Collectionmentioning
confidence: 99%